Formulation And Test Of Antioxidants And Effectiveness Of Toner Preparations From Pumpkin Fruit Extract (Cucurbita Moschata Duch) Using The Dpph (2,2 Diphenyl - 1-Picrylhydrazyl) Method - Nora Pereira Pinto Nora Pereira Pinto; Tatiana Siska Wardani; Bangkit Riska Pertama (CV. AFDIFAL MAJU BERKAH, 2026)
Pumpkin (Cucurbita moschata Duch.) is rich in natural antioxidants to overcome skin xerosis which has a high prevalence in Indonesia, but stable toner formulations are still limited. This study aims to develop a pumpkin extract toner and test its antioxidant activity. This type of quantitative experimental research with variations in extract concentration (0%, 5%, 10%, 20%). The population of fresh fruit from Karanganyar, simplicia samples and 9 female panelists aged 20-25 years. Instruments include a rotary evaporator, pH meter, skin moisture meter, UV-Vis spectrophotometer; SPSS analysis (One-Way ANOVA) and IC50 DPPH regression. The results showed that all formulas met physical standards (pH 4.6-5.6, homogeneous, non-irritant, moisture 46-55%), with very strong IC50 (F0: 44.02 µg/mL; F1: 40.19; F2: 39.65; F3: 38.86 µg/mL), a positive dose-response trend. Formula F3 is optimal as a natural antioxidant toner.